Coordinated Dynamic Use of Dispersed Flexibility to Maximize the Time-variant Aggregated Potential for Redispatch. Issue 2 (2020) - Müller, Benjamin; Lens, Hendrik
Abstract: During recent years, the European interconnected transmission system has been affected by a significant increase of grid congestion. Nowadays, large-scaled power plants are providing redispatch power, but will be phased out in coming decades. Besides this development, new technologies like renewable energies or battery storage systems emerged in power systems. These technologies are typically small-scaled, dispersed and connected to distribution systems. Dispersed generation units, storage systems, electric vehicles, and controllable loads may be capable of providing flexible power. Coordinated dynamic use of flexible power from large numbers of small units could become a key contribution to cope with grid congestion in the future. The paper presents a methodology to determine the maximum, time-variant potential for redispatch of distributed units aggregated in a virtual power plant. It is based on parameter-based optimization and takes into account dynamic and energy capacity related constraints. Moreover, the constraints of distribution and transmission systems as well as the impact on power flows is considered and investigated for multiple scenarios by using linearized power flow sensitivities.